2002
DOI: 10.1248/cpb.50.1341
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Hyaluronate-hydroxyethyl Acrylate Blend Gel and Release of Cationic Amphiphilic Solutes.

Abstract: Hyaluronate-hydroxyethyl acrylate blend gel (HA-PHEA) were prepared to modify the brittleness of hyaluronate gel (HA) and the characteristics of HA-PHEA gel were compared with those of HA and polyhydroxyethyl acrylate (PHEA) gels. These gels were high in water content and transparent. HA-PHEA gel was improved in viscoelastic properties due to the elasticity and the high affinity with water of PHEA, and the drying-swelling cycles became reversible. The effective charge densities q q of the gels estimated from m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…UV radiation-induced polymerization is also frequently used to prepare hydrogels [ 92 , 93 , 94 , 95 ]. With this type of polymerization, they can be formed in situ [ 96 ], molded structures and even photoreversible systems can be prepared that photodegrade on exposure to UV light such that the release of drugs is controlled [ 97 ].…”
Section: Cross-linking Strategies To Obtain Chemical Hydrogelsmentioning
confidence: 99%
“…UV radiation-induced polymerization is also frequently used to prepare hydrogels [ 92 , 93 , 94 , 95 ]. With this type of polymerization, they can be formed in situ [ 96 ], molded structures and even photoreversible systems can be prepared that photodegrade on exposure to UV light such that the release of drugs is controlled [ 97 ].…”
Section: Cross-linking Strategies To Obtain Chemical Hydrogelsmentioning
confidence: 99%
“…Due to the rapid photo-cross-linkable property, HA-MA hydrogel has been extensively used in tissue engineering applications, such as 3D cell culture scaffolds, drug/protein delivery, wound healing material, and corneal perforation sealing material . Generally, the methacryloyl group can be conjugated to HA chains using methacrylic anhydride ,,, or glycidyl methacrylate (Scheme A). ,,, Using the methacrylic anhydride method in an aqueous phase, a high molar ratio of methacrylic anhydride (20 equiv) is required, and a compromised substitution degree (SD; ≤20%) is normally achieved, due to the low solubility of methacrylic anhydride in H 2 O. ,,,, To increase SD, Rachel Auzély-Velty et al reported methacryloyl conjugation method using a mix solution of H 2 O and dimethylformamide (DMF) for dissolving HA and methacrylic anhydride, resulting in 49% of SD . Similarly, Spencer L. Fenn and Rachael A. Oldinski utilized an ion-exchange resin and a mixed solution of H 2 O and dimethyl sulfoxide to increase the solubility of HA and methacrylic anhydride .…”
Section: Introductionmentioning
confidence: 99%